Transformations 7 roles to drive change by design - Yee, Joyce; Jefferies, Emma; Michlewski, Kamil; Ayre, Kate (Amsterdam, The Netherlands BIS Publishers, 2017)
Tracking how design has changed in previous book "Design Transitions" has inevitably led the authors to explore how organisations are changing using design. Design is now the key driver of innovation and change within organisations across the globe. It is therefore important to learn how, when and why to use design to drive change in your organisation. "Transformations" documents how design is being used to support change across different organisations, countries and sectors, sharing the stories of experts in their fields at varying stages of their transformative journeys. The authors present seven roles for change that are used to influence the development of products and services, the shape of the organisation itself and, most importantly, their ability to embrace change. These seven roles can transform organisations to be more innovative, human-centred and resilient: Cultural Catalyst; Framework Maker; Humaniser; Power Broker; Friendly Challenger; Technology Enabler and Community Builder.
Keywords: Industrial design; Organizational change; Organizational change -- Case studies; Design -- 21st century